2004
DOI: 10.1111/j.0013-9580.2004.28302.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII Deficiency Associated with Valproate Treatment

Abstract: Summary:Purpose: We present two children who developed a deficiency of factor XIII with valproate (VPA) treatment. This coagulation disorder has not been described in association with VPA treatment in children, and only very recently in one adult patient.Results: Both patients showed recurrent epistaxis as major clinical sign of a combination of decreased coagulation parameters (factor XIII deficiency with thrombocytopenia and decreased von Willebrand factor, respectively). A few days after reduction or withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 8 publications
0
15
0
4
Order By: Relevance
“…Gerlach et al [3] found the relative risk of developing a postoperative haematoma in neurosurgical patients with postoperative factor XIII activity under 60%. Another study by Teich et al [12], found that factor XIII activity of below 70% was associated with severe haemorrhage for epilepsy surgery.…”
Section: Introductionmentioning
confidence: 97%
“…Gerlach et al [3] found the relative risk of developing a postoperative haematoma in neurosurgical patients with postoperative factor XIII activity under 60%. Another study by Teich et al [12], found that factor XIII activity of below 70% was associated with severe haemorrhage for epilepsy surgery.…”
Section: Introductionmentioning
confidence: 97%
“…We asked that severe side effects such as hepatopathy, pancreatitis, encephalopathy, and coagulation disorders, [4][5][6] and also minor side effects such as weight gain, fatigue, change in hair color, and hair loss, be reported. We tried to obtain the fi les of anonymous patients to analyze the clinical details whenever possible.…”
Section: Methodsmentioning
confidence: 99%
“…3 Most of the side effects are mild and transient. However, more serious adverse reactions can occur, such as hepatotoxicity, 4 hyperammonemic encephalopathy, 5 coagulation disorders, 6 and pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…VPA has been reported to induce thrombocytopenia, abnormal platelet function, hypofibrinogemia, von Willebrandlike disorders, and a decrease in vitamin K-dependent factors [74][75][76]. Teich et al reported a case of two patients who developed spontaneous bleeding while being treated with VPA.…”
Section: What Occurs With Valproic Acid Toxicity?mentioning
confidence: 99%
“…Teich et al reported a case of two patients who developed spontaneous bleeding while being treated with VPA. Laboratory findings attributed the coagulopathy to factor XIII deficiency which returned to baseline upon discontinuation of the drug [74]. Although this side effect has been known for approximately 30 years, there have been several disagreements with regards to the clinical relevance of VPA-associated changes in coagulation.…”
Section: What Occurs With Valproic Acid Toxicity?mentioning
confidence: 99%